Kingdom of the Netherlands : Netherlands Antilles; Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper for the Kingdom of the Netherlands reports the Antillean economy lacks natural resources and is open and undiversified, relying mainly on exports of services such as tourism, international financial services, shipping, and oil refining. Exports and domestic consumer spending, both private and public, drove the economic recovery. Economic growth in the United States and the appreciation of the euro against the national currency contributed to the strong performance in the tourism sector.